Force or Core Principles of Peacekeeping? A Normative Dilemma for Contemporary UN Peace Operations - Wilbert Augustin Ibuge (Technium Social Sciences Journal, 2026)
The core principles of United Nations peacekeeping operations (UNPKOs), namely, consent of the parties to the conflict, impartiality, and non-use of force except in self-defence or in the defence of the mandate, have traditionally helped to underpin the deployment and employment in United Nations Peace Operations (UNPOs), particularly when missions were deployed under Chapter VI of the UN Charter, which relates to peaceful settlement of disputes. However, although most UNPOs today are deployed under Chapter VII of the UN Charter, which concerns the use of force or “peace enforcement”, the requirement to adhere to the core trinity of UNPKOs principles remains in place. This is also the case for the Force Intervention Brigade (FIB) deployed in the DRC since 2013 to date. Mandated to use offensive force against armed groups (AGs) deemed as “negative forces” even proactively, the FIB’s offensive authority, both unprecedented and exceptional, has clearly challenged the utility of the trinity of peacekeeping principles, particularly when their usage is invoked in environments such as the DRC, where there is no peace to keep. This raises critical questions regarding the alignment of offensive military action with the UN’s traditional peacekeeping norms (Karlsrud, 2015; de Coning et al., 2016). This article examines the dilemma between the FIB’s targeted use of offensive force and the expectations to adhere to the core peacekeeping principles. The article interrogates the changing nature and patterns of UNPOs and the ongoing normative and doctrinal tensions emerging from their applications in complex conflict environments (de Coning, 2020; Karlsrud, 2021), with a view to propose measures to help address those tensions.